The structure, composition, and threatened plants in The Kinarum Protected Forest, South Kalimantan, Indonesia - dodo dodo; Syamsul Hidayat (Society for Indonesian Biodiversity, 2020)
Abstract. Dodo, Hidayat S. 2020. The structure, composition, and threatened plants in The Kinarum Protected Forest, South Kalimantan, Indonesia. Biodiversitas 21: 2603-2618. Kinarum Protected Forest (Kinarum PF) is one of the remaining tropical forest areas in Tabalong District, South Kalimantan, Indonesia. It is feared that deforestation will occur in this forest due to various human activities. The research was conducted to determine the structure and composition of vegetation in Kinarum PF which several decades ago was once a forest concession area. This research also explored the existence of threatened, endemic, and protected plants. Research has been carried out using the track plot method. The total research area is 0.6 ha consisting of three transect lines with five plots measuring 20 x 20 m2 each transect. Data were analyzed with important value index (IVI), dominance index, species diversity index, and species abundance index. The results recorded 460 specimens belonging to 121 species, 86 genera, and 43 families. Most species are from the family Lauraceae followed by Moraceae and Rubiaceae. The results also recorded 42 species included in the IUCN red list plants, eight of which are classified as threatened plants, namely Aglaia angustifolia, Artocarpus tamaran, Dracontomelon costatum, Durio dulcis, Durio kutejensis, Eusideroxylon zwageri, Myristica magnifica, and Shorea guiso. These plants have an average IVI value less than 10% and the species abundance index is close to zero. In general, the forest condition is classified as moderate with a diversity index value at each growth stage in the range of values ??1-3. However, IVI of each species, especially those belonging to the threatened, endemic, and protected plants are on average low.